Aspects of Contemporary Dental Practice - Shakarashvili, Marina; Arabuli, Mania (European Scientific Journal, ESJ, 2017)
Contemporary dentistry is a high-tech field that constantly improves treatment and prevention practices of dental problems. Dentistry is one of the most prestigious, demanded and highly paid specializations in the field of medicine. However, the evidence increasingly suggests that dental practitioners are exposed to sustainable occupational stress and often suffer from burnout syndrome. These negative aspects are closely related to the nature of the work itself – introduction of new technologies, long-term contact with a high number of patients and lack of patient-physician time. Lack of high standards of professional health lead to worsening of health status (mental and physical). Many of the existing problems physicians are facing are related to patients, while issues that patients are having are related to their subjective perception of health care. Therefore, in the binary doctorpatient relationship both parties should adapt to each other: physician as his/her profession requires and patient – as he/she has a problem treatable by the physician.